2019
DOI: 10.1177/0193945919852426
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor Support and Affective Organizational Commitment: The Mediator Role of Work Engagement

Abstract: The aim of the study was to verify the mediator role of work engagement between supervisor social support and affective organizational commitment. A cross-sectional and correlational study using questionnaires was conducted. We obtained a convenience sample of 267 participants from 403 nurses from two public hospitals (66.25% response rate). Participants were required to be registered nurses without a supervisor position and to have worked for at least 1 year in the same ward in a public hospital. The mediator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
3
13
2
Order By: Relevance
“…On the other hand, as a finding of this research, it can be claimed that supervisor support is more significant in mitigating feelings of cynicism. In this regard, studies have found that lack of supervisor support reduces employee's commitment [54] and their desire to remain in the organization [55], causing the appearance of health problems and harming the general feelings of well-being at work [56], which in turn, leads to attitudes of cynicism in the work environment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as a finding of this research, it can be claimed that supervisor support is more significant in mitigating feelings of cynicism. In this regard, studies have found that lack of supervisor support reduces employee's commitment [54] and their desire to remain in the organization [55], causing the appearance of health problems and harming the general feelings of well-being at work [56], which in turn, leads to attitudes of cynicism in the work environment.…”
Section: Discussionmentioning
confidence: 99%
“…Engaged employees have high levels of energy and are enthusiastically involved in their work . Past studies have found that highly engaged employees demonstrate greater organizational commitment (Orgambídez & Almeida, 2020), exhibit more positive behaviors (Wang et al, 2019), experience lower levels of physical and psychological distress (Kunie et al, 2017;Oshio et al, 2018), and report weaker intentions to leave (Rafiq et al, 2019). Past studies have also found that antecedents such as rewards (Keyko et al, 2016;Mukaihata et al, 2019), job control (Keyko et al, 2016;Oshio et al, 2018), social support (Cao & Chen, 2019;García-Sierra et al, 2016), and self-efficacy (Bakker & van Wingerden, 2021) predict greater work engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Harman's single factor test was applied in Jamovi® to examine CMV bias and to avoid any erroneous conclusions (Orgambídez & Almeida, 2019). An unrotated factor solution of PCA shows that the first factor merely accounts for 24% of the total variance which is less than the 50% cutoff value.…”
Section: Methods Sample and Proceduresmentioning
confidence: 99%